A derivational approach to the interpretation of scrambling chains - Saito, Mamoru (Lingua, 2003)
Japanese (and Korean) scrambling is known for its unique properties. It freely applies long-distance, but does not establish an operator-variable relation like the standard cases of A′-movement. It is also distinct from NP-movement in that its trace exhibits strict proper binding effects. Further, as observed by Tada [1990, Scrambling(s). MS., MIT] among others, it shows a pattern similar to Hindi scrambling with respect to binding: A phrase preposed by clause-internal scrambling can serve as an A-binder, but one preposed by long scrambling cannot. The purpose of this paper is to discuss these properties in some detail and to suggest a unified analysis for them. First, I assume, following Tada, that scrambling to sentence-initial positions is subject to total reconstruction, implementing the idea with a slightly modified version of Chomsky's (1993, A minimalist program for linguistic theory. In: Hale, K., Keyser, S.J. (Eds.), The View from Building 20: Essays in Linguistics in Honor of Sylvain Bromberger. MIT Press, Cambridge, MA) copy and deletion analysis of movement. This accounts for the “semantically vacuous” nature of scrambling. Then, building on the insights of Kitahara (2000, Case and scrambling: a derivational view. MS., Keio University), I propose that the total reconstruction applies derivationally. This explains the A/A′ asymmetry observed with clause-internal scrambling and long-distance scrambling. Finally, I argue that the proper binding effects on scrambling require an independent condition, and suggest its formulation as a constraint on the application of Merge. If the analysis proposed in this paper is on the right track, Japanese (and Korean) scrambling does not have subtypes like A-scrambling and A′-scrambling, but is a uniform operation with well-defined abstract properties. The most fundamental among them is the radical (total) reconstruction property. It is this property that makes scrambling exhibit patterns that are quite different from operator movement and NP-movement.